SKALA KESANTUNAN BENTUK TUTURAN DIREKTIF BERDASARKAN PERSEPSI SISWA DI SMAN 1 SURAKARTA - Nurul Masfufah (Universitas Muhammadiyah Surakarta, 2012)
The involvement of politeness in directive speech especially at school environment is an interesting phenomenon to be studied. This study aims to assess the perception of politeness in directive speech by students of SMAN 1 Surakarta. This research involves the combination of descriptive quantitative and qualitative method. The data is collected through questionnaires and is analyzed by descriptive statistical techniques. The results show the orders of politeness from the most polite to the least polite as follows: (1) directive speech in the form of advice, (2) directive speech in the forms of question, (3) directive speech in the forms of a strong signal, (4) directive speech in the forms of subtle cues, (5) the form of directive speech in the form of mitigated statements, (6) directive speech in the form of imperative statements, (7) directive speech the form of expression of interest, (8) directive speech with explicit statements, and (9) directive speech with the imperative modes.